Equity Stakes and Hold-up Problems - Rick Harbaugh (Claremont McKenna College, Department of Economics, 2001)
Equity ties between businesses change the division of the firms' joint profits, thereby affecting incentives for relation-specific investments and other strategic actions. Depending on which side owns the equity and how readily the equity can be resold, we find that the changed incentives can resolve all four types of holdup-related problems: underinvestment, overinvestment, undercooperation, and sabotage. Equity stakes indirectly affect bargaining over the joint profits by making the bargaining positions of the firms dependent on each other. For instance, if one firm is made unprofitable by a breakdown in negotiations, the other firm loses as well. Since bargaining positions are linked, each firm benefits less from attempts to grab a larger share of the joint profits by strengthening its relative bargaining position, and benefits more from actions that increase joint profits. While both firms can gain from increased efficiency due to the equity stake, firms in many cases should only acquire an equity stake if they can bargain for a discounted price.
Keywords: L14; L22; G31; G32; G34; C78; 330; equity blocks; subsidiaries; gainsharing; partial ownership; business groups; ESOPs